2017
DOI: 10.1017/s0967199417000582
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid in the modulation of oocyte and preimplantation embryo development

Abstract: Potential reproductive effects are considered as the major aspect of biomolecules functionality in an organism. The recent identification of differential patterns of fatty acids across ovarian follicles and their association with levels of sexual maturity highlights the importance of these biomolecules. It is well known that fatty acids are highly diverse in terms of their functional properties. Oleic acid is chemically classified as an unsaturated omega-9 fatty acid. Besides serving as an important energy sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 96 publications
(170 reference statements)
0
29
0
Order By: Relevance
“…A recent review by Fayezi et al [54] outlined the most likely mechanisms through which OA exerts its protective effects. These included but were not limited to 1) altering triacylglycerol (TAG) synthesis, 2) reducing oxidative stress, and 3) altering energy production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review by Fayezi et al [54] outlined the most likely mechanisms through which OA exerts its protective effects. These included but were not limited to 1) altering triacylglycerol (TAG) synthesis, 2) reducing oxidative stress, and 3) altering energy production.…”
Section: Discussionmentioning
confidence: 99%
“…PA and OA differentially affect LD accumulation. Since OA is steatotic and causes lipid accumulation, exposure to OA increases LD number [47,54]. LDs are made up of a phospholipid monolayer surrounding a neutral lipid core mainly consisting of TAGs [55].…”
Section: Discussionmentioning
confidence: 99%
“…FAs is one of energy source and it is contained in cytoplasm of porcine and bovine oocytes (McKeegan and Sturmey, 2011). Recently, many studies had reported that dietary supplement of PUFAs in cattle could enhanced reproductive performance (Wathes et al, 2007) and addition of oleic acid in maturation medium supported the development of oocyte via inhibition harmful effects of saturated FAs (Wang and Tsujii, 1999; Leroy et al, 2003; Aardema et al, 2011; Yenuganti et al., 2016; Fayezi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Formation of the zygote and embryo development after fertilization are considered as marker of the developmental ability in oocytes (Fayezi et al, 2018). During the maturation of the oocyte, incomplete cytoplasmic maturation results in polyspermy and lower development of embryos in vitro (Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary n-3 fatty acids have been reported to influence the follicular status and to increase the cleavage rate of oocytes (Zachut et al 2010). In vivo investigations on oocyte and embryo development have revealed that regular intake of unsaturated fatty acids has improving effects on oocyte maturation and embryo development (Fayezi et al 2018). Fatty acids can also modulate granulosa cell proliferation and steroidogenesis in vitro (Maillard et al 2018), by which may influence cumulus-oocyte complexes (COCs) maturation.…”
Section: Discussionmentioning
confidence: 99%